The Relationship between The Teaching Style of Pysical Education Teacher with Student Motivation of Learning Movement - Syani Sunardi Mauludin; Bambang Abduljabar; Nuryadi Nuryadi (Journal of Physical Education For Secondary Schools, 2021)
The purpose of this study was to determine the relationship between the teaching style of Physical Education teachers with students' motivation to learn motion in vocational high schools. The method used is descriptive method. The population in this study were physical education teachers and class XI. In the sampling of this study were 4 physical education teachers with saturated sampling techniques and class XI MM 2 at SMKN 1 Katapang using simple random sampling. This study used a teaching style questionnaire for Physical Education teachers and a questionnaire on students' motivation to learn motion. The results of this study indicate a correlation of 0.72 which has a strong relationship and there is a significant relationship marked with t-hitungÂ = 4,29 t-tabelÂ = 2,78. So it can be concluded that there is a relationship between the teaching style of Physical Education teachers with the motivation to learn movement of students at SMK Negeri 1 Katapang.